Palma Alvarado, Daniel Ladrones. Historia social y cultural del robo en Chile, 1870-1920, Santiago, LOM, 2011. (320 páginas) ISBN: 978-956-00-0225-9 - Brangier, Víctor (Estudios Avanzados, 2011)
Palma Alvarado, Daniel Ladrones. Historia social y cultural del robo en Chile, 1870-1920, Santiago, LOM, 2011. (320 páginas) ISBN: 978-956-00-0225-9